Effect of short-term resistance training on corticospinal and reticulospinal excitability in biceps brachii - Tanel, Meghan (2023)
BACKGROUND: Descending pathways, such as the corticospinal (CST) and reticulospinal tracts (RST), are highly influential structures that mediate movement. Although the two tracts have differences in their motor function (Lemon 2008), it has been postulated that both may contribute to neural adaptations to short-term resistance training (Siddique et al. 2020; Glover & Baker 2020). Studies using transcranial magnetic stimulation (TMS), a non-invasive form of brain stimulation, to measure intracortical and CST adaptations to resistance training have yielded equivocal results (Siddique et al. 2020). The effect of resistance training on RST excitability has yet to be investigated in humans. Therefore, the aim of this study was to measure adaptations of the CST and RST to a 6-week resistance training program. Two forms of resistance training (explosive and sustained contractions) were implemented to ascertain whether motor pathway adaptations are modulated by training type.